A hybrid multi-constraint lagrangian relaxation based aggregated cost based segment routing in qos aware software defined networks - Gopal, Kumar Parop; Sambath, M. (Vietnam Journal of Science and Technology, 2025)
The rise of Software Defined Networking (SDN) increases routing flexibility and offers a more efficient method of balancing network flows. Because of the economic and technological challenges of shifting to a fully SDN-enabled network, the prevalent network design has been a hybrid SDN network architecture with partially deploying SDN switches in a traditional network. As the need for efficient and dependable network services in Software Defined Networks (SDNs) grows, guaranteeing Quality of Service (QoS) has become a significant concern. This study presents a new technique, "Hybrid Multi-constraint Lagrangian Relaxation based Aggregated Cost (HMLR-AC) Segment Routing," to handle the QoS-aware routing problem in SDNs. The HMLR-AC Segment Routing method combines the benefits of both Lagrangian Relaxation (LR) and Aggregated Cost (AC) strategies to improve routing decisions. Furthermore, an H-permissible Paths Routing Scheme (HPRS) effectively routes traffic flows under path cardinality constraints. It seeks to reduce total network costs while meeting numerous QoS restrictions such as bandwidth, latency, and reliability. It also includes the idea of H-permissible pathways, which are paths that match the given QoS standards, providing high-quality service delivery. By leveraging the centralized control plane and decoupling the data plane, the proposed method HMLR-AC exploits the programmability and flexibility of SDNs. It uses a global network perspective and real-time traffic statistics to dynamically change routing decisions in response to changing network conditions. This allows for more effective resource use and traffic load balancing, which leads to better network performance. Extensive simulations are run using a typical network situation to assess the efficacy of the HMLR-AC Segment Routing system. Regarding QoS satisfaction, network cost, and scalability, the findings show that our proposed HMLR-AC outperforms existing routing systems. The suggested system significantly improves resource usage, network congestion avoidance, and overall user experience.